EXPERIMENTAL VALIDATION OF A COMPUTATIONAL PROGRAM FOR SIMULATING HYBRID SOLAR AND GAS WATER HEATING SYSTEMS - Lafay, J. M. S.; Krenzinger, A. (Revista de Engenharia Térmica, 2007)
This work presents the methodology and results of the validation of a computer program for the simulation of water heating systems combining solar energy and gas. Two experimental systems, named series and parallel, were assembled. These systems have the same components, differing on how they are connected. All the components were individually characterized and their parameters determined. Simulations of the behavior of the thermal tank, gas heater and solar collector were performed and confronted to experimental data. The results show that the simulation program “AQUESOLGAS” can accurately describe the behavior of water heating systems with solar energy and gas.